Current and Future Perspectives of Ethnomathematics as a Program - Rosa, Milton; D’Ambrosio, Ubiratan; Orey, Daniel Clark; Shirley, Lawrence; Alangui, Wilfredo V.; Palhares, Pedro; Gavarrete, Maria Elena (ICME-13 Topical Surveys,, 2016)
This survey on the modernity of ethnomathematics addresses numerous themes related to both ethnomathematics and mathematics education. It offers a broader view of mathematics, including ideas, procedures, concepts, processes, methods, and practices rooted in distinct cultural environments. In addition, by reflecting on the social and political dimensions of ethnomathematics, another important aspect of this research program is the development of innovative approaches for a dynamic and glocalized society. Ethnomathematics recognizes that members of different cultures develop unique mathematical techniques, methods, and explanations that allow for an alternative understanding and transformation of societal norms. The theoretical basis of ethnomathematics offers a valid alternative to traditional studies of history, philosophy, cognition, and pedagogical aspects of mathematics. The current agenda for ethnomathematics is to continue an ongoing, progressive trajectory that contributes to the achievement of social justice, peace, and dignity for all. The debates outlined in this book share a few of the key ideas that provide for a clearer understanding of the field of ethnomathematics and its current state of the art by discussing its pedagogical actions, its contributions for teacher education, and its role in mathematics education.